Photon Upconversion Nanomaterials - Zhang, Fan (Springer, 2015)
Starting from the late 1990s, the field of photon upconversion nanomaterials has undergone significant expansion and has become one of the most active research areas within the nanoscience community. Exciting developments have been made at a very fast pace by many research groups. The vast number of papers published on upconversion nanomaterials over the past two decades clearly witness it, which has increased exponentially, with most of the activity and development happening in the last 10 years. These kinds of materials can emit ultraviolet/visible/near-infrared light under near-infrared excitation (anti-Stokes emission). This unique optical property precludes background fluorescence and light scattering from biological systems. The emission of multiple and narrow emission lines is an additional hallmark of upconversion nanoparticles that opens up new avenues for optical applications. In the past decades, the related theories, methods and techniques have been explored. As a consequence, novel photon upconversion materials are increasingly emerging, and their applications extend from traditional fields, for example, optical communication amplifiers and solid-state lasers to high-tech fields, including biotechnology, sensors, solar cell and photocatalysis, etc. Researchers can therefore give a deep insight into the synthesis strategies, pathways, and phenomena for photon upconversion nanomaterials, and in particular, establish the relationship for structure—function—synthesis...